Insulating Modernism : Isolated and Non-isolated Thermodynamics in Architecture - Moe, Kiel (Birkhäuser, 2014)
What is the best way to achieve sustainable energy savings in buildings? The mainstream construction industry has been saying for decades: it’s insulation. Today there is a growing movement among architects who claim that, by contrast, it isintelligent design thatprovides the best energetic results. This book describes the history, theory and facts of the mainstream insulation technology and the emerging alternative design approaches.